LTTE's online network and its implications for regional security - Shyam Tekwani (2009)
In the light of expanding online networks of terrorist groups and the immediate and foreseeable threat they represent both to the sovereignty of nations and the security of the critical and informational infrastructures, the case for securitization of the internet is a valid and urgent one. This paper will use the case study of the online network of the LTTE to demonstrate how online networks pose a security threat and how securitization of the internet can offer solutions.